2016
DOI: 10.1097/jcp.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Effects of a Single Dose of Ayahuasca in Patients With Recurrent Depression

Abstract: Ayahuasca is an Amazonian botanical hallucinogenic brew which contains dimethyltryptamine, a 5-HT2A receptor agonist, and harmine, a monoamine-oxidase A inhibitor. Our group recently reported that ayahuasca administration was associated with fast-acting antidepressive effects in 6 depressive patients. The objective of the present work was to assess the antidepressive potentials of ayahuasca in a bigger sample and to investigate its effects on regional cerebral blood flow. In an open-label trial conducted in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
434
0
22

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 408 publications
(502 citation statements)
references
References 26 publications
18
434
0
22
Order By: Relevance
“…Flavia de Lima Osorio and colleagues (Osorio et al, 2015) and Rafael Sanches and colleagues (Sanches et al, 2016), both working in Sao Paulo, Brazil, reported studies where a single dose of ayahuasca to patients with recurrent depression. In Osorio's pilot study, 6 medication and ayahuasca naive participants (4 women) were given 2.2 ml/kg of a standardised preparation of ayahuasca containing 0.8 mg/ml DMT and 0.21 mg/ml of harmine.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavia de Lima Osorio and colleagues (Osorio et al, 2015) and Rafael Sanches and colleagues (Sanches et al, 2016), both working in Sao Paulo, Brazil, reported studies where a single dose of ayahuasca to patients with recurrent depression. In Osorio's pilot study, 6 medication and ayahuasca naive participants (4 women) were given 2.2 ml/kg of a standardised preparation of ayahuasca containing 0.8 mg/ml DMT and 0.21 mg/ml of harmine.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
“…Three pilot studies using psychedelics in major depressive disorder have been published to date in the modern literature (Carhart-Harris et al, 2017, 2016aOsorio et al, 2015;Sanches et al, 2016). Our own open-label pilot study gave 2 doses of psilocybin (a 10 mg "test" dose and a 25 mg therapeutic dose) 1 week apart with psychological support before and after the experience to 20 patients with treatment resistant depression who were moderately to severely depressed, but without psychotic features (Carhart-Harris et al, 2017, 2016a.…”
Section: Modern Clinical Studiesmentioning
confidence: 99%
“…Regarding anxiolytic and antidepressive effects in humans, a double-blind, placebo-controlled studies with nine experienced ayahuasca users showed that a single ayahuasca dose was associated with less panic symptoms and reduced hopelessness 41 . An open-label study by our group showed that a single ayahuasca dose was associated with rapid and sustained reductions in anxiety and depressive symptoms in 17 patients with treatment-resistant major depressive disorder 42 . The anxiolytic and antidepressive effects were observed already in the first hours after ayahuasca intake and remained significant for 21 days.…”
Section: Therapeutic Potentialsmentioning
confidence: 99%
“…Evidence from uncontrolled studies 42,48,49 Anxiolytic Antidepressive Antiaddictive Evidence from controlled studies 41,43 Anxiolytic Antidepressive…”
Section: Table 3 Main Therapeutic Potentials Of Ayahuascamentioning
confidence: 99%
“…Ayahuasca is an Amazonian botanical hallucinogenic cook. It contains dimethyltryptamine, a 5-HT2A receptor agonist, and harmine, a monoamine-oxidase A inhibitor [10,11] As a partial agonist of mu opioid receptor, buprenorphine can diminish the level of depression and suicidal thoughts rapidly [12,13].…”
Section: Introductionmentioning
confidence: 99%